1995
DOI: 10.1111/j.1600-051x.1995.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of partial and full mouth scoring of plaque and gingivitis in oral hygiene studies

Abstract: Bentley CD, Disney JA: A comparison of partial and full mouth scoring of plaque and gingivitis in oral hygiene studies, J Clin Periodontol 1995; 22: 151-135. © Munksgaard, 1995. Abstract, The clinical testing necessary to demonstrate the safety and efficacy of new toothbrushes is complex and expensive. Any moditication of methodology that could reduce complexity and cost without compromising quality would benefit both investigators and the public. Results from an 8-week toothbrush study were assessed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 7 publications
2
43
0
1
Order By: Relevance
“…Bentley and Disney evaluated the comparison of partial and full‐mouth scores of plaque and gingivitis without compromising study quality. Their analyses showed that all‐teeth, the Ramfjord teeth, half mouth and molars/anteriors revealed a similar pattern as whole‐mouth and proximal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Bentley and Disney evaluated the comparison of partial and full‐mouth scores of plaque and gingivitis without compromising study quality. Their analyses showed that all‐teeth, the Ramfjord teeth, half mouth and molars/anteriors revealed a similar pattern as whole‐mouth and proximal areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the study a partial-mouth model (Bentley and Disney, 1995) was used. Two contra-lateral randomly chosen quadrants (www.random.org) served for the collection of dental plaque biofilm that was not disturbed by scoring or the disclosing solution (one in the upper and one in the lower jaw; Heijnsbroek et al, 2006; Van Leeuwen et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…2). At the start of the preexperimental phase (day 0), subjects were assessed for the clinical parameters BOMP, plaque, gingival abrasion, and stain using a partial‐mouth scoring model 23 . All teeth in two randomly chosen contralateral quadrants (one upper and one lower quadrant) were examined except for third molars.…”
Section: Methodsmentioning
confidence: 99%